2016
DOI: 10.14238/sp9.4.2007.227-32
|View full text |Cite
|
Sign up to set email alerts
|

Usia Awitan Pubertas dan Beberapa Faktor yang Berhubungan pada Murid SD di Kota Padang

Abstract: Latar belakang. Latar belakang. Latar belakang. Latar belakang. Latar belakang. Beberapa penelitian mendapatkan kecenderungan usia awitan pubertas akhir-akhir ini menjadi lebih cepat dari beberapa tahun yang lalu. Banyak faktor yang mempengaruhinya antara lain ras, indeks massa tubuh (IMT), tingkat sosial ekonomi, penyakit kronis dan sebagainya. Tujuan. Tujuan. Tujuan. Tujuan. Tujuan. Mengetahui rerata usia awitan pubertas anak laki-laki dan perempuan di daerah urban dan sub-urban kota Padang, mengetahui apaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Several studies also found associations between onset of puberty and BMI. 1,4,12 Some studies also showed correlations between adolescent BMI and pubertal onset. 25,26 A 2008 study reported that a one-unit increase in age between 2 and 8 years was associated with sooner growth spurt at puberty, approximately ±0.6 years in boys and ±0.7 years in girls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies also found associations between onset of puberty and BMI. 1,4,12 Some studies also showed correlations between adolescent BMI and pubertal onset. 25,26 A 2008 study reported that a one-unit increase in age between 2 and 8 years was associated with sooner growth spurt at puberty, approximately ±0.6 years in boys and ±0.7 years in girls.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 This situation occours due to the possibility of increasing socioeconomic conditions, nutrition, psychologic stimulation, health, urban and rural areas. [2][3][4] Changes in attitude and behavior towards a more advanced and healthy lifestyle, as well as diet and nutrition, have impacted the health of certain groups. Obesity has impact on child develop, including onset of puberty.…”
mentioning
confidence: 99%
See 1 more Smart Citation